Pemanfaatan Pangan Berbasis Kearifan Lokal dalam Upaya Pencegahan Anemia Defisiensi Besi pada Ibu Hamil di BPM Muzilatulnisma Kota Jambi - Patriani, Sirly; Sinulingga, Selpyani (Jurnal Abdimas Kesehatan (JAK), 2024)
Anemia is the biggest public health problem in the world, especially among pregnant women. Anemia occurs due to a lack of iron and folic acid in the body. Women who suffer from anemia during pregnancy have the potential to give birth to babies with low birth weight. Besides that, anemia can cause death of both mother and baby during the birth process. The impact of iron deficiency during pregnancy can be risky for the mother and fetus, bleeding occurs and the fetus can cause LBW. To prevent anemia in pregnant women, the pharmacological method is by consuming Fe tablets and the non-pharmacological method is by consuming foods that contain iron from animal ingredients and vegetable ingredients such as nuts, green vegetables, tofu and tempeh, etc. Apart from that, efforts that can be made are anemia counseling and screening. The aim of this community service is to provide educational knowledge about the use of food based on local wisdom in an effort to prevent iron deficiency anemia. This community service activity was carried out at the Muzilatulnisma Independent Practice Midwife, the target of this community service was pregnant women with a total of 15 people.  Sinta accredited national journal publication output target. The method used was to carry out health education by providing counseling using leaflets which was carried out on July 18 2023. The results obtained were an increase in knowledge after being provided with education.